ANALYSIS OF TRACE ELEMENT CONCENTRATIONS IN ARTICHOKES AT DALAT USING TOTAL REFLECTION X-RAY FLUORESCENCE - Nguyễn Thị Minh Sang; Phạm Thị Ngọc Hà; Nguyễn Thị Nguyệt Hà; Nguyễn An Sơn (Tạp chí Khoa học Đại học Đà Lạt)
Artichokes, which provide a lot of nutrients and minerals, are a specialty of Dalat. In our investigation, artichokes were collected at two artichoke farms in Ward 12 of Dalat from 2nd to 16th February 2020. Artichoke stems, leaves, flowers, and roots were studied with the Total Reflection X-ray Fluorescence (TXRF) technique. Twelve artichoke samples were collected, three samples for each part of the artichoke. TXRF technique is commonly used in qualitative and quantitative analyses of element compositions in solid, liquid, and gas samples. The main benefits of TXRF include simplicity, rapid measurement, simultaneous determination of the concentrations of many elements, small sample size, and no matrix effects. This study aimed to determine the concentrations of inorganic elements in locally grown artichokes. Concentrations of eleven trace elements, P, K, Ca, Mn, Fe, Cu, Zn, As, Cd, Hg, and Pb, are presented in the results. Most elements have concentrations similar to those found in previous studies, except for cadmium, which is notably higher.